Alcohol-Dependent Inpatients in Northern Vietnam: A Follow-Up Study on Relapse and Co-Occurring Psychiatric Disorders - Nguyen, Thi Phuong Mai; Kim, Bao Giang; Nguyen, Van Tuan (European Journal of Mental Health, 2020)
Background: The prevalence of alcohol dependence has been increasing in several countries in the world as well as in Vietnam. This study aims to describe relapse among alcohol-dependent inpatients in Northern Vietnam and some co-occurring psychiatric disorders in these patients.Methods: This study followed 53 alcohol-dependent patients who were treated for six months at the Vietnam National Institute of Mental Health. At the point of one month, three months, and six months after being discharged from the hospital, the patients were monitored for their alcohol consumption, relapse into alcohol dependence, and co-occurring psychiatric disorders by clinical psychiatrists, using the International Classification of Diseases, the 10th edition, Hamilton depression rating scale, Hamilton anxiety rating scale, Pittsburgh Sleep Quality Index, and the EQ-5D-5L Life Quality Assessment.Results: The prevalence of relapse into alcohol dependence was 81.1%. The highest relapse rate was found in the first month after alcohol withdrawal (46.5%), then it decreased gradually. 53.9% of the relapsed patients had at least four alcohol withdrawals; they mainly used home-brewed alcohol. The average daily alcohol intake was fairly high: 14.4 ± 8.5 standard drinks. Mental disorders such as depression, anxiety, and sleep disorder were very prevalent among patients with relapsed alcohol dependence.Conclusions: The rate of relapsed alcohol dependence in Northern Vietnam was very high. It is important to detect and treat psychiatric disorders simultaneously with alcohol dependence to achieve better treatment effectiveness and reduce relapse rates.